The Sisters Grimm : The Unusual Suspects - Book 2 - Buckley, Michael; Ferguson, Peter 1968- (New York : Amulet Books, 2005)
Although filled with anger over her parents' disappearance, eleven-year-old Sabrina Grimm--along with her grandmother, sister, and several fairy-tale characters--tries to discover who has killed her teacher.
Keywords: Characters and characteristics in literature -- Fiction; Anger -- Fiction; Sisters -- Fiction; Grandmothers -- Fiction; School stories; Fiction